The Waiter's Handbook - Brown, Graham; Hepner, Karon (Singapore, 2009)
This book continues to be an excellent resource for those in the hospitality industry. It has been updated to address the requirements in the new SIT07 Hospitality, Tourism and Events Training Package and changes in the industry. The book is a comprehensive training guide to modern food and beverage service. It explains the technical and interpersonal skills required by today's waiters for all types of establishments, from casual bistros to formal dining. New sections have been added to address changes to the smoking laws and cultural and special dietary
Keywords: Waiters-Handbooks